Feeding Deterrence to Reticulitermes speratus (Kolbe) by Fibroporia radiculosa (Peck) Parmasto 1968 - Nadia Nuraniya Kamaluddin (Insects, 2017)
Brown rot fungus Fibroporia radiculosa (Peck) Parmasto grown in decayed wood and non-wood material, potato dextrose agar (PDA) media, deterred Reticulitermes speratus (Kolbe) feeding. Decayed wood and PDA media were extracted and tests were performed to assess termite feeding behavior towards the extracts. We found that the extract from PDA media also suppressed termite feeding, although it did not induce mortality. Using gas chromatography and mass spectrometry analysis, two bioactive compounds were detected from the decayed wood extract, and one was detected from the PDA extract. Based on National Institute of Science and Technology (USA) Mass Spectral library match and compound fragmentation, both of the compounds belong to the sesquiterpenes family.